The future teacher personality forming in Krestovozdvizhensk Labour Fraternity of Nickolay Neplyuev (Pedagogy of Higher and Secondary Education, 2013)
Rud O. N. The future teacher personality forming in Krestovozdvizhensk Labour Fraternity of Nickolay Neplyuev.The article deals with the educational system of Nickolay Neplyuev The features of future teacher personality forming in Krestovozdvizhensk Labour Fraternity are found out.
Keywords: Krestovozdvizhensk Labour Fraternity; future teacher personality forming; aesthetic education; religious education; moral education; mental development